Photochemical inactivation of chikungunya virus in human apheresis platelet components by amotosalen and UVA light - Tsetsarkin, Konstantin A.; Sampson-Johannes, Adam; Sawyer, Lynette; Kinsey, John; Higgs, Stephen; Vanlandingham, Dana L. (My University, 2013)
Chikungunya virus (CHIKV) is a mosquito-borne alphavirus that recently re-emerged in Africa and rapidly spread into countries of the Indian Ocean basin and South-East Asia. The mean viremic blood donation risk for CHIKV on La Réunion reached 1.5% at the height of the 2005–2006 outbreaks, highlighting the need for development of safety measures to prevent transfusion-transmitted infections. We describe successful inactivation of CHIKV in human platelets and plasma using photochemical treatment with amotosalen and long wavelength UVA illumination. Platelet components in additive solution and plasma units were inoculated with two different strains of high titer CHIKV stock (6.0–8.0 logs/mL), and then treated with amotosalen and exposure to 1.0–3.0 J/cm² UVA. Based on in vitro assays of infectious virus pre- and post-treatment to identify endpoint dilutions where virus was not detectable, mean viral titers could effectively be reduced by > 6.4 ± 0.6 log[subscript 10] TCID[subscript 50]/mL in platelets and ≥ 7.6 ± 1.4 logs in plasma, indicating this treatment has the capacity to prevent CHIKV transmission in human blood components collected from infected donors in or traveling from areas of CHIKV transmission.
Keywords: Chikungunya virus; Transfusion-transmitted infections; Amotosalen; CHIKV